Wybrane aspekty funkcji emocjolnalno-ekspresyjnej Wspólnoty AA oraz programów terapeutycznych - Trzebiatowski, Jakub (Wydawnictwo Naukowe UAM, 2008)
The research conducted by the author of the article among AA patients and among alcohol-and-substances abuse facility patients shows that the actions of the AA society are based on a clearly defined program, and are more effective than those taken by the alcohol-and-substances abuse facility. AA members rated their life quality higher than patients of the facility did. Their AA membership allowed them to fulfil their emotional needs, such as understanding, support, and help in battling crises.
Selected aspects of the emotional-expressive function of the A A Society and therapeutic programs